Algorithmic you. Un design-setting per la riappropriazione dei dati personali attraverso narrazioni poetiche e rivisitando mo-delli di poesia visiva - Andrea Benedetti; Ángeles Briones; Arianna Bellantuono (Ocula)
The article describes an educational activity that uses personal data to create a poetic narrative and reflect on the relationship between humans and technology. "Poetic narratives," built on the concept of "infopoetry," transform data into evocative narratives through visual, audiovisual, and material languages. The main goal is to aesthetically represent data as a means of expression and interaction with technology. The activity is part of a Communication Design course at Politecnico di Milano, which focuses on: information design, data visualization, statistics, and semiotics for a critical approach to data and design. "Algorithmic you" explores the design of narrative objects to contemplate data rather than analyze it. Students are invited to collect their personal data from everyday devices and platforms, such as pictures on their phones or data on social media, and concepts such as mirrors and glitches guide the inquiry to narrate with objects that straddle art and design their own experience and relationship with technology. The activity encourages students to reappropriate and reframe data to design an expressive language that explores the complex relationships between people, data, and algorithms. Student work examples show various data design practices, such as transforming text into images or vice versa.